2022
DOI: 10.1007/s13347-022-00543-1
|View full text |Cite
|
Sign up to set email alerts
|

Does AI Debias Recruitment? Race, Gender, and AI’s “Eradication of Difference”

Abstract: In this paper, we analyze two key claims offered by recruitment AI companies in relation to the development and deployment of AI-powered HR tools: (1) recruitment AI can objectively assess candidates by removing gender and race from their systems, and (2) this removal of gender and race will make recruitment fairer, help customers attain their DEI goals, and lay the foundations for a truly meritocratic culture to thrive within an organization. We argue that these claims are misleading for four reasons: First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The potential role for AI in crafting LORs has been previously suggested; however, this is the first study that demonstrates the feasibility of this application for AI 12,13 . Human‐authored letters have documented, problematic tendencies toward bias, and AI is suggested as a potential solution to reducing bias in LOR, though contrary arguments and data exist 3,11,14–18 . Although our study only examined biased language related to gender and was not powered to examine this aspect in detail, we observed signal of gender‐biased language in both human and AI‐authored LORs.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The potential role for AI in crafting LORs has been previously suggested; however, this is the first study that demonstrates the feasibility of this application for AI 12,13 . Human‐authored letters have documented, problematic tendencies toward bias, and AI is suggested as a potential solution to reducing bias in LOR, though contrary arguments and data exist 3,11,14–18 . Although our study only examined biased language related to gender and was not powered to examine this aspect in detail, we observed signal of gender‐biased language in both human and AI‐authored LORs.…”
Section: Discussionmentioning
confidence: 68%
“…12,13 Human-authored letters have documented, problematic tendencies toward bias, and AI is suggested as a potential solution to reducing bias in LOR, though contrary arguments and data exist. 3,11,[14][15][16][17][18] Although our study only examined biased language related to gender and was not powered to examine this aspect in detail, we observed signal of gender-biased language in both human and AI-authored LORs. Current and future work in understanding AI systems' bias will hopefully further determine whether AI can mitigate or exacerbate bias in letter writing.…”
Section: Discussionmentioning
confidence: 99%
“…The other half of this process is recommendation letter reading and interpretation. Regardless of self-generated text or AI-assisted generation of text, there is a history of bias in AI-supported hiring [ 43 ]. Even human screeners are not immune to this bias, tending to carry biases when they, for example, perceive a name to be identifying a person's gender or race [ 44 , 45 ].…”
Section: Llms For Letters Of Recommendationmentioning
confidence: 99%
“…Despite these findings, many researchers have sounded the alarm. For instance, Drage and Mackereth (2022) , in their review of assertions made by AI providers, suggested that endeavors to eradicate gender and race from AI frequently misinterpret these concepts as discrete characteristics rather than broader structures of power, or that that using AI as a fix for gender diversity issues, an example of technosolutionism, fails to address the inherent systemic issues within organizations. Others raise concerns that algorithms could unintentionally exacerbate existing biases within recruitment processes ( Kelly-Lyth, 2021 ).…”
Section: Algorithms As a Solution Against Biasmentioning
confidence: 99%